Preventing heat stress with different feeding methods in laying hens - Ertas, ON; Şahin, Kazım (Tubitak Scientific & Technological Research Council Turkey, 2002)
In this study, the effects of different density diets (15% HP, 2700 kcal/kg ME, Diet N; 18% HP, 3025 kcal/kg ME, Diet Y), and different feeding methods on yield, egg quality, blood acid-base balance, serum metabolites, and nutrient digestibility were determined in laying hens at heat stress. Sixteen-week-old hens (Ross Brown) were divided into 6 group of 30 hens each and study was conducted in a 3 x 2 factorial experimental design. The diets were given to animals by three methods during heat stress. The feeding methods were as follows. Both diets were given to hens through traditional ways (Control Group N and Y): during the hottest hours of the day, feed withdrawal was conducted and the darkening was excluded (Withdrawal Group N and Y); and the house was darkened by black curtains between 1400-1800 and feed withdrawal was not done Darkening Group N and Y. During the treatments, diets and feeding methods had significant effects on feed intake (p<0.01). The highest body weight, egg yield, egg shell thickness, egg shell weight and egg specific gravity was determined in the darkening group, followed by the feed withdrawal and control group (p<0.01). Feeding methods were positive effects on egg formation, egg yolk formation, Haugh units, blood pH, PCO2 and pHCO(3) concentration (p<0.01), but diets had no effect (p>0.05). In addition, serum metabolites were affected positively by darkening the house. On the other hand, digestibility of nutrient values were higher in the darkening group than in the withdrawal and control groups (p<0.01). These results indicate that darkening the house between 14(00) and 18(00) at heat stress had an increase in performance, egg production and quality and nutrient digestibility of laying hens.
Yumurta tavuklarinda sicaklik stresinin farkli yemleme yöntemleriyle önlenmesi
Keywords: heat stress; egg production; serum metabolites; digestibility